2013
DOI: 10.1016/j.str.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Substrate-Induced Conformational Changes of the Secondary Citrate/Sodium Symporter CitS Revealed by Electron Crystallography

Abstract: The secondary Na+/citrate symporter CitS of Klebsiella pneumoniae is the best-characterized member of the 2-hydroxycarboxylate transporter family. The recent projection structure gave insight into its overall structural organization. Here, we present the three-dimensional map of dimeric CitS obtained with electron crystallography. Each monomer has 13 a-helical transmembrane segments; six are organized in a distal helix cluster and seven in the central dimer interface domain. Based on structural analyses and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Some superfamilies, such as MFS, can harbor antiporters and symporters with similar transporter architectures (reviewed in Ref. ), and similar architectures can be accommodated by sequences with very low similarity, as reported recently in the case of two citrate transporters from TC classes 2.A.11 and 2.A.47 . TctA proteins display less than 15% identity with any of the crystallized transporters deposited in the Protein Data Bank (PDB) .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Some superfamilies, such as MFS, can harbor antiporters and symporters with similar transporter architectures (reviewed in Ref. ), and similar architectures can be accommodated by sequences with very low similarity, as reported recently in the case of two citrate transporters from TC classes 2.A.11 and 2.A.47 . TctA proteins display less than 15% identity with any of the crystallized transporters deposited in the Protein Data Bank (PDB) .…”
Section: Introductionmentioning
confidence: 92%
“…15), and similar architectures can be accommodated by sequences with very low similarity, as reported recently in the case of two citrate transporters from TC classes 2.A.11 and 2.A.47. 16 TctA proteins display less than 15% identity with any of the crystallized transporters deposited in the Protein Data Bank (PDB). 17 Therefore, any exercise in structure modeling must consist of threading the sequence of the protein over plausible structural templates.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in the case of citrate carrier (CitS), which was recently shown to share a similar architecture with VcINDY, substrate-activated structural changes observed in electron microscopy projection maps include no conformational changes in these helices. This indicated that they act as a stator with little or no functional role (47). The fact that both NaPi-IIa repeats align to the equivalent structurally repeated regions in VcINDY (i.e., the C-terminal segment of each repeat, Fig.…”
Section: Identifying a Structural Homolog Of Napi-iiamentioning
confidence: 99%
“…However, there are conflicting data regarding exact stoichiometry 7, 1619 . The structure of Kp CitS has been studied extensively by electron crystallography, providing a glimpse of its global structure and a clue to the substrate-induced conformational changes 20, 21 . The crystal structure of a homologous symporter from Salmonella enterica ( Se CitS) recently revealed that it forms an asymmetric dimer, and that each protomer embeds a substrate translocation pathway at the interface between the transport and the dimerization domains 22 .…”
Section: Introductionmentioning
confidence: 99%